2017
DOI: 10.1200/jco.2017.35.15_suppl.9022
|View full text |Cite
|
Sign up to set email alerts
|

NGS to reveal heterogeneity between cerebrospinal fluid and plasma ctDNA among non-small cell lung cancer patients with leptomeningeal carcinomatosis.

Abstract: 9022 Background: In current clinical setting, NSCLC patients harboring specific driver mutation were usually treated guiding by prior profiling of the primary tumor when developed to brain metastasis. Some studies have shown that circulating tumor DNA (ctDNA) derived from cerebrospinal fluid (CSF) can reveal unique genomic alterations present in brain malignancies. We assessed CSF as a liquid biopsy media and compared to matched plasma. Methods: We performed capture-based ultra deep sequencing on ctDNA derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It would also have been interesting to evaluate whether the brain lesions differed from the lung lesion in the genetic actionability profile. In this regard, genetic testing of cerebrospinal fluid could have been considered [25].…”
Section: Discussionmentioning
confidence: 99%
“…It would also have been interesting to evaluate whether the brain lesions differed from the lung lesion in the genetic actionability profile. In this regard, genetic testing of cerebrospinal fluid could have been considered [25].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of CSF ctDNA has also shown gene mutations associated with therapy resistance [15,27,64]. Drug-resistance mutations in patients whose CNS disease progressed during TKI therapy (EGFR, ALK, HER2, or BRAF) were identified in CSF ctDNA in one-third of cases [27].…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…In metastatic melanoma spreading to the leptomeninges, CSF examination using PCR-based techniques has been successfully used for diagnosis and monitoring response to therapy based on the detection of driver mutations, e.g. affecting BRAF [64,75].…”
Section: Leptomeningeal Metastases Diagnostic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the T790M mutation has not been identified neither in BM or LM [44,45] , nor in CSF of patients who have developed LM following EGFR TKIs [46] . Jiang et al [47] reported a lower frequency of T790M mutation (21%) and a higher frequency of MET amplification (39%) in the CSF, suggesting that MET amplification could confer a major risk of leptomeningeal invasion [48] .…”
Section: Target Dosage/day Csf Level (Nmol/l) Penetration (Csf/plasmamentioning
confidence: 99%